Of Sugar and Snow : A History of Ice Cream Making - Quinzio, Jeri (Book collections on Project MUSE., 2009)
Was ice cream invented in Philadelphia? How about by the Emperor Nero, when he poured honey over snow? Did Marco Polo first taste it in China and bring recipes back? In this first book to tell ice cream's full story, Jeri Quinzio traces the beloved confection from its earliest appearances in sixteenth-century Europe to the small towns of America and debunks some colorful myths along the way. She explains how ice cream is made, describes its social role, and connects historical events to its business and consumption. A diverting yet serious work of history, Of Sugar and Snow provides a fascinat.